Pain and Anxiety Experience in the Choice of Epidural Analgesia in Delivery - Lidija Fumić Dunkić; Gorka Vuletić (Acta Clinica Croatica, 2021)
The experience of labor pain is a complex process that represents the interaction of the nociceptive stimulus within the physiologic process with a series of psychological factors. The aim of this study was to investigate the relation between the choice of epidural analgesia as a form of pain management and psychological state of woman in labor; moreover, whether the women in labor with a higher level of anxiety have a more intensive experience of pain during labor and therefore decide on epidural analgesia. Pain was evaluated by the visual analog scale, while the sensory and affective pain components were evaluated by the McGill Pain Questionnaire, and anxiety as a trait was measured with the State-Trait Anxiety Inventory-form X. Women in labor with a higher level of anxiety had a significantly increased affective component of pain, but did not significantly more frequently decide on labor with epidural analgesia. The women having chosen epidural analgesia experienced more intense pain during delivery before epidural analgesia, with the sensory component of pain being less pronounced in the women in labor without epidural analgesia, while there was no difference in the affective component of pain.